Accuracy assessment of digital impressions with varied scanning paths in partially edentulous ridges with mobile abutment teeth: An in vitro comparative study - Samar S. Alaghbari; Esraa A. M. Saeed; Lu Zhen; Mohammed M. Al Moaleem; Hongjie Chen; Bayan M. Gashan; Shaojie Dong; Lin Niu; Bo Hu (PLoS ONE, 2025)
Background Periodontal prosthesis or removable partial dentures are essential treatments for partially edentulous dentition with periodontal issues. This study aimed to assess the accuracy of digital impressions obtained through an intra-oral scanner, employing different scanning paths versus conventional impressions in partially edentulous ridges with mobile abutment teeth. Methods Eight lower Kennedy class I and class III models were employed as test models. The abutment teeth in these models were subjected to various mobility grades, according to the Miller classification. Reference data was generated by scanning the test models using an extra-oral laboratory scanner. An intra-oral scanner (TRIOS 4; V21; 3Shape A/S) was used to obtain ten digital impressions following two different scanning paths (Scan path A and Scan path B). For conventional impressions, two impression materials (Monophase polyether and Polyvinyl siloxane) were used to create ten impressions with a one-step technique. Working stone casts were produced and converted to digital data. Accuracy was assessed by analyzing the deviation between test data (digital and conventional data) and the reference data using 3D software (Geomagic Control X). The data was analysis using sequential tests, including two-way and one-way ANOVA, and paired t-tests (p < 0.05). Results Digital impressions obtained through an intra-oral scanner exhibited significantly higher accuracy. Within the digital impression category, those recommended by the manufacturer obtained using scan path A showed lower deviations than those acquired through scan path B. Considering the degree of tooth mobility, models with GII and GIII mobile RPD abutment teeth displayed significantly higher deviations (p < 0.001) than those with G0, GI across all impression techniques. The accuracy of conventional impressions with GII and GIII mobility was clinically unacceptable (deviation >200µm). Conclusion For partially edentulous cases with mobile abutment teeth, digital impressions exhibited superior accuracy for G0, GI. Following the manufacturer-recommended scanning protocol in scan path A can improve the accuracy of impressions. Furthermore, if there is persistent mobility, particularly in GII and GIII, the use of final conventional impressions is forbidden.